Extending an approach to hospital malnutrition to community care. - Moynihan, Paula; Macdonald, Alastair; Teal, Gemma; Methven, Lisa; Heaven, Ben; Bamford, Claire (British Journal of Community Nursing, 2012)
This feature investigates the potential relevance to community care of a new food provision and nutritional management system for older hospital patients. A qualitative study identified the core factors contributing to inadequate food intake in older patients in hospital, including: poor mealtime ambience; lack of necessary mealtime assistance; inflexible meal provision; lack of monitoring of nutrient intake and absence of accountability in nutritional care. Many of these factors are also relevant to older people living in the community. To address these issues, we designed a new system for the nutritional care of the older patient: 'hospitalfoodie'. Hospitalfoodie facilitates: patient nutritional screening; patient-tailored food choice; and information exchange among the healthcare team. The system introduces a more flexible approach to provision of food, including the development of nutrient-dense 'mini meals' for older patients. The system facilitates monitoring of patient food intake against their nutrition targets and alerts staff of nutrition shortfalls. The relevance of components of hospitalfoodie to community nutritional care was explored through qualitative interviews and focus groups with a range of care providers.